Development and psychometric properties of short form of central sensitization inventory in participants with musculoskeletal pain: A cross-sectional study. - Tomohiko Nishigami; Katsuyoshi Tanaka; Akira Mibu; Masahiro Manfuku; Satoko Yono; Akihito Tanabe (PLoS ONE)
Background The central sensitization inventory (CSI) comprises 25 items and is commonly used to measure somatic and emotional symptoms related to central sensitization symptoms. CSI was developed as an easy-to-administer screening instrument for patients at high risk of developing central sensitization in whom it was essential to quickly evaluate the condition. The purpose of the present study was to develop a short form of CSI and evaluate its psychometric properties using a contemporary approach called Rasch analysis. Methods A total of 505 patients with musculoskeletal disorders were recruited in this study. The CSI, pain intensity, pain interference, and the health-related quality of life (QOL) were evaluated for each participant. The original CSI items were consecutively analyzed using the Rasch model. Successive Rasch analyses were performed until a final set of items satisfied the model fit requirements. We also analyzed the psychometric properties of the original and short forms of CSI. Results Four consecutive Rasch analyses identified the removable items. Finally, the shortest questionnaire obtained that maintained the correct psychometric properties based on the Rasch model contained only 9 items (CSI-9). Rasch analysis showed that the CSI-9 had acceptable internal consistency, exhibited unidimensionality, had no notable differential item functioning, and was functional on the category rating scale. Conclusions The nine-item short form of CSI has acceptable psychometric properties and is suitable for use for patients with musculoskeletal pain. Thus, the CSI-9 can be used as a brief instrument to evaluate central sensitization.